THE ORIGIN OF GRAPEVINE CULTIVATION IN ITALY: THE ARCHAEOBOTANICAL EVIDENCE - Marvelli, S.; De’ Siena, S.; Rizzoli, E.; Marchesini, M. (Annali di Botanica, 2013)
Grapevine remains show that this plant has been important for humans since ancient times. This paper presents a synthesis of archaeobotanical studies on grapevine remains (pollen, wood, charcoal, seed/fruit and other botanical remains) from Epigravettian to Bronze Age sites. Carpological remains are the most important ones, because they often allow to distinguish cultivated and wild grapevines. Grapevine findings are rare in Mesolithic sites, they increase during Neolithic period and become frequent in Bronze Age. Archaeobotanical data show that during Neolithic and in the Early Bronze Age a good level of knowledge concerning grapevine utilization was already acquired; during Middle and Late Bronze Age the grapevine diffusion increases. Based on archaeobotanical data, the wild grapevine evolution by indigenous people was probably accompanied by an input of allochtonous vines from Mycenaean world, and then from Hellenic world. Therefore, the critical period of grapevine domestication can be placed between Bronze Age and Early Iron Age.